Aesthetics and Participation in Accessible Art Experiences: Reflections on an Action Research Project of an Audio Guide - Reviers, Nina; Hanoulle, Sabien (Journal of Audiovisual Translation, 2023)
The action research project titled A Touch of Museum to Scale aims to improve the accessibility of the Museum to Scale art collection at the University of Antwerp. This project collaborates with various stakeholders to prototype tactile objects and an inclusive art guide for five artworks. It seeks to engage users of diverse abilities, investigate universal access services, and promote the integration of accessibility and artistic creation. The audio guide integrates visual descriptions and information for people with and without a visual impairment and integrates the artistic contributions of artists with and without disabilities. Artists also create tactile objects, which are an artistic and tactile translation of original artwork and a piece of art in their own right. The authors discuss project activities, such as personal observations, interviews, questionnaires, brainstorming sessions, and theoretical considerations based on literature and experience. The research is exploratory and invites both researchers and practitioners to reflect on participation and the aesthetics of access. Lay summary A Touch of Museum to Scale is a practice-based project that aims to improve the accessibility of the Museum to Scale art collection at the University of Antwerp. By working with various stakeholders, the team developed a prototype of tactile objects and an inclusive art guide for five artworks. This project is an experiment, in which we address several pertinent questions: how to create an audio guide that engages diverse abilities? How to make a guide that can be used by all? How to bring accessibility and artistic creation closer together? The result is an audio guide that combines visual descriptions and information for people with and without a visual impairment. It also includes the artistic contributions of artists with and without disabilities. In addition to the audio guide, artists have created tactile artworks to complement the original collection. In this text, the authors discuss the project activities and link them to insights from scientific literature. The authors hope to inspire a deeper reflection about accessibility and aesthetics in accessible art.